Transdisciplinary approach as a resource to develop student metacognitive skills in studying physical and engineering disciplines - A. B. Iskakova; K. A. Nurumzhanova (Russian State Vocational Pedagogical University, 2024)
Introduction. The article presents the results of a study of the actual problem in applying a transdisciplinary approach as a modern educational resource that contributes to improving the efficiency and productivity of students' learning outcomes based on increasing their cognitive activity, due to the purpose of forming metacognitive skills in the educational process.Aim. The current study aims to assess the effectiveness of the transdisciplinary approach to the creation of integrated didactic content of physical and engineering disciplines as a didactic resource to develop engineering thinking in students through the formation of metacognitive skills.Methodology and research methods. The authors' concept of the study is to actualise the transdisciplinary principle for the mobilisation and disclosure of the possibilities of the content and technologies of integrated study of physical, mathematical and general engineering disciplines for the formation of students' meta-skills At the same time, the authors assumed that engineering meta-skills are a special type of integrated skills and an integral personal characteristic of an engineer, allowing him/her to more effectively carry out professional activities in the conditions of rapid development of new technologies, when it is not the increase and updating of knowledge, but the desire to manage, comprehend cognitive potential based on mobile transdisciplinary knowledge and systems that are actualised special "meta", "hard" and "soft" skills. The ascertaining and forming stages of the pedagogical experiment were carried out. At the ascertaining stage of the experiment, in order to assess the level of formation of engineering thinking among students, an optimal list of basic criteria was developed as a criterion-diagnostic apparatus, in which the measured variable is the completeness and level of evaluation of educational achievements obtained by students when performing a system of transdisciplinary constructivist case tasks. At the formative stage of the experiment with the participation of 316 students of different years of study at Toraighyrov University, an assessment of the effectiveness of the application of transdisciplinary content of general engineering disciplines was carried out in two stages.Results. The results of the pedagogical experiment confirmed the effectiveness of the transdisciplinary approach to the development of integrated didactic content of general engineering and physical-mathematical disciplines. In the experimental group, in the level of formation of engineering meta-skills among students, the greatest difference was observed between the indicators of formation of thinking components related to engineering and design (18 %) and cognitive (64 %) aspects. The transdisciplinary approach has less influence on the instrumental aspect of solving engineering problems, which proves that both traditional and transdisciplinary training are primarily aimed at the formation of instrumental skills. As a result of experimental teaching, future engineers have increased cognitive motivational awareness in the process of solving engineering problems.Scientific novelty. The integrated didactic content of general engineering disciplines was developed on the basis of the transdisplinary principle; additions were made in the form of constructivist case studies that contribute to the development of students' metacognitive skills applied with other skills when solving engineering problems; and the cognitive structure and content of the concept of "engineering thinking" were concretised.Practical significance. The developed case-workshop of tasks to be used in experimental training is quite variable and can be applied in the practical line of any integrated physical and engineering discipline.